Traffic- and health-related problems of older drivers : a case study based on police licence suspension records - Peräaho, Martti; Suomi. Liikenne- ja viestintäministeriö (Reports and memoranda / Ministry of Transport and Communication, 2003)
Abstract (kuvailulehti). Summary (s. 8).
Keywords: liikenneturvallisuus; ikääntyminen